2011
DOI: 10.1177/0733464811420563
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Functional Capacity Among Centenarians

Abstract: This study investigated correlates of functional capacity among participants of the Georgia Centenarian Study. Six domains (demographics and health, positive and negative affect, personality, social and economic support, life events and coping, distal influences) were related to functional capacity for 234 centenarians and near centenarians (i.e., 98 years and older). Data were provided by proxy informants. Domain-specific multiple regression analyses suggested that younger centenarians, those living in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 49 publications
0
15
0
2
Order By: Relevance
“…The study is limited by its cross-sectional design, which prevents the examination of predictors of ADL independence over time. The accuracy of self-reported instruments may be compromised by low cognition and literacy, fatigue, and reduced sensory function (Arosio et al, 2017;Martin et al, 2018;Poon et al, 2007), although informant-based instruments addressed these limitations to some degree (Martin et al, 2013). and physical performance were also correlated with IADL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study is limited by its cross-sectional design, which prevents the examination of predictors of ADL independence over time. The accuracy of self-reported instruments may be compromised by low cognition and literacy, fatigue, and reduced sensory function (Arosio et al, 2017;Martin et al, 2018;Poon et al, 2007), although informant-based instruments addressed these limitations to some degree (Martin et al, 2013). and physical performance were also correlated with IADL.…”
Section: Discussionmentioning
confidence: 99%
“…Centenarians have long been regarded as a unique population because their longevity offers an important resource for studying healthy aging (Perls et al, 1999;Richmond, Law, & Kay-Lambkin, 2011) and the complex interactions among multiple pathological changes which concertedly affect the manifestation of clinical symptoms (Tanprasertsuk et al, 2019). While the centenarians studies are limited, the existing findings indicate that ADL independence in centenarians are affected by sensory functioning (Martin et al, 2018), race, age, education, self-reported health (Poon et al, 1992), and living arrangement (Davey et al, 2010;Mao & Han, 2018;Martin et al, 2013;Poulain & Herm, 2016). Cognition was found to affect ADL independence among centenarians in Japan (Arai et al, 2014), but others suggested that maintaining a good level of cognition was not sufficient to achieve IADL independence (Motta et al, 2008) and the prevalence of cognitive impairment in centenarians is reduced (Andersen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of centenarians in the United States are focused on either genetic (Hadley et al 2000; Perls and Terry 2003; Zeng et al 2010; Murabito et al 2012; Sebastiani et al 2012) or psychological (Adkins et al 1996; Hagberg et al 2001; Margrett et al 2010; Martin et al 2010; Murabito et al 2012) aspects of survival to advanced ages. On the other hand, several theoretical concepts suggest that early-life events and conditions may have significant long-lasting effect on survival to advanced ages.…”
Section: Introductionmentioning
confidence: 99%
“…O mesmo autor destaca que estudos populacionais longitudinais têm encontrado resultados diferentes, sugerindo elevada morbidade (especialmente em mulheres), 5 enquanto outros autores encontraram elevados níveis de dependência funcional e declínio cognitivo sugestivo de demência. 6,7 Além do evidente predomínio feminino entre os centenários, as mulheres apresentam maior probabilidade de serem portadoras de múltiplas síndromes geriátricas e maior prevalência de doenças musculoesqueléticas e déficits sensoriais. 6,7 A prevalência de demência entre os centenários parece ser superior a 58%, enquanto 54% são portadores de artrite/artrose.…”
unclassified
“…6,7 Além do evidente predomínio feminino entre os centenários, as mulheres apresentam maior probabilidade de serem portadoras de múltiplas síndromes geriátricas e maior prevalência de doenças musculoesqueléticas e déficits sensoriais. 6,7 A prevalência de demência entre os centenários parece ser superior a 58%, enquanto 54% são portadores de artrite/artrose. 5 Os centenários procuram mais os serviços de emergência por pneumonia e quedas do que idosos não centenários, e evoluem mais frequentemente com óbito nessas unidades.…”
unclassified